2011
DOI: 10.1186/1756-0500-4-528
|View full text |Cite
|
Sign up to set email alerts
|

Health state utilities of a population of Nigerian hypertensive patients

Abstract: BackgroundEstablishment of the health impact of hypertension on quality of life of Nigerians is a step towards controlling the disease. The study aimed to provide a Nigerian specific reference list of utility scores of hypertensive patients with various interacting conditions.FindingsAn interviewer-based, cross-sectional study was conducted using hypertensive patients in two purposively selected tertiary hospitals located in South-Eastern Nigeria. Health Utility Index Mark 3 (HUI3) was used.A total of 384 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…In a Swedish population with high BP, health-state utility was 0.73 when using a rating scale and 0.81 when using TTO [ 6 ]. In a Nigerian hypertensive population, it was relevantly lower at 0.35(+/-0.42), using the HUI3 method [ 23 ]. Again, these comparisons should be interpreted cautiously because different instruments and methods were applied [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a Swedish population with high BP, health-state utility was 0.73 when using a rating scale and 0.81 when using TTO [ 6 ]. In a Nigerian hypertensive population, it was relevantly lower at 0.35(+/-0.42), using the HUI3 method [ 23 ]. Again, these comparisons should be interpreted cautiously because different instruments and methods were applied [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…16 Stroke patients imposed the greatest HRQoL deficit among all other co-morbidities in both IG and CG. The HRQoL deficit associated with stroke and hypertension has been reported by Ekwunife et al 17 Antihypertensive drug induced Headache and antiplateletic drug induced gastritis, were the most adverse reactions observed in intervention group during the study period which showed a consistent pattern in study conducted by Gholami et al and Singhal Rohit et al 18 Patients with more than one diseases and with polypharmacy had poor quality of life which showed a similar result in study conducted by Divaldo pereira et al 19 about pharmaceutical care in elderly, in which there was a positive correlation between number of diseases and number of comorbidities with QOL.…”
Section: Discussionmentioning
confidence: 75%
“…The health related quality of life weights for the different states (non-symptomatic, stroke, and CHD) were obtained from the data of a health utility state assessment carried out in Nigeria [8]. To obtain the QALYs which represent the clinical outcome, the weights were multiplied by the number of life years spent in the different states, and then averaged over a life time of 30 years with a utility discount of 3%.…”
Section: Methodsmentioning
confidence: 99%